Exposure and disease burden of fumonisins and aflatoxins from sorghum consumption in Ethiopia - Sadik, J.A.; Fentahun, N.; Brouwer, Inge D.; Tessema, M.; Fels-Klerx, H.J.van der (Elsevier, 2026)
Studies on mycotoxin exposure from sorghum consumption and related public health risk estimation are rarely available in Ethiopia. The aim of this research was to assess fumonisin and aflatoxin exposure of adults through sorghum consumption in the Amhara National Regional State (ANRS) and at national level in Ethiopia and to estimate related health risks. Data on fumonisin and aflatoxin concentrations in sorghum samples were collected from a survey and literature. Estimated fumonisin exposure in the ANRS and at national level were below the FAO/WHO limit of 2000 ng/kg bw day to be considered a health concern. The estimated aflatoxin exposure levels in the ANRS and at national level fall below the Margin of Exposure value of 10000, indicating potential health concern. The incidence of hepatocellular carcinoma due to aflatoxin exposure in the ANRS ranges from 0.0003 to 0.017 while at national level, it ranges from 0.181 to 8.47 (per100.000 persons/year). The related disability-adjusted life years estimates for the ANRS and at national level ranged from 0.0003 to 0.019 and 0.204 to 11.230, respectively. Aflatoxin exposures were driven more by sorghum intake than aflatoxin contamination. Dietary intervention could further reduce the health risk estimates.